Impacts of Coarse Atmospheric Particulate Matter Between 2.5 and 80 mu m on Respiratory Admissions in Heraklion, Crete Island, Greece - Bleta, A.; Nastos, P. T.; Kaminski, U.; Dietze, V. (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
{The goal of this study is to quantify the impact of airborne coarse particles between 2.5 and 80 mu m (PM2.5-PM80) on hospital admissions for respiratory diseases, acquired from the two main hospitals in Heraklion, Crete Island. The atmospheric coarse particles were collected in Heraklion city from November 18, 2011 to May 31, 2013, using the Sigma-2 passive sampler technique. Further, the Scanning Electron Microscopy (SEM), was utilized to identify the qualitative structure of PMs. On one hand, we applied Generalized Addictive Models (GAMS) in order to assess the impact of coarse particles on respiratory diseases. The findings of the analysis revealed that the highest estimates were 7.3 % (Cl: 1.00-1.01) and 7.1 % (Cl: 1.00-1.01) increases in weekly respiratory admissions associated with an increase of 10 mu g m(-3) with respect to coarse particles between 10 and 20 mu m, for men and women, respectively. On the other hand, using SEM technique, the PMs were identified by means of their chemical composition. It is worth noting the presence of Rutile (a mineral composed primarily by Titanium Dioxide), which was found in our samples with possible origin from Saharan desert, causing adverse respiratory problems.}